Histochemical Studies on the Testis of Adult Bakerwali Goat (Capra hircus) - Bashir, Shagufta; Sarma, Kamal; Suri, Shalini; Devi, J; Kamil, S (Indian Journal of Veterinary Anatomy, 2012)
The present study was conducted to localize various histochemicals moieties in the testis of adult Bakerwali goats which revealed moderately diffused reaction for glycogen particles in the capsule. The spermatogenic cells and the cytoplasm of the Sertoli cells revealed weak to moderate reactions. The basement membrane and the lining epithelium of the tubuli recti and rete testis showed mild and moderate reactions to glycogen, respectively. The spermatogenic cells of the seminiferous tubules and the Sertoli cells were Feulgen reactive. The ovoid or spherical nuclei of the lining cells of the tubuli recti and rete testis revealed mild to moderate Feulgen reaction.